KETAKSTABILAN MEMANJANG KAPAL BERSAYAP SEBELUM TINGGAL PERMUKAAN - H. Priyatno, Dany; Iskendar, Iskendar (Badan Pengkajian dan Penerapan Teknologi, 2006)
Wing in Surface Effect (WiSE) craft or winged ship is a peripatetic transportation floating to surface by exploiting dynamic cushion because surface effect influence and form of the means wing. This craft adopted high speed planning hull for its fuselage hullform design, the lateral and longitudinal instability always occurs during planing mode operations. In this paper the study and investigate both theoretical and experimentals of longitudinal dynamic instability done, especially the porpoising fenomena of the high speed craft in the water territory. Porpoising is the effect as a self-sustained coupled motion of pitching and heaving.